Research and Critical Review of Sahar Yousafzai’s Short Stories - Seemab, Sher Zaman; Mukhtiar, Paghunda; Tahir, Muhammad (sourcecoder, 2023)
Professor Sahar Yousaf Zai is a respectable name in Urdu short story. He was born in Farhat Abad, Swat on Oct, 20, 1935. He has contributed a great deal to Urdu literature. He was awarded the presidential award in 1962. His book of short story "Aag Awar Saye" was highly praised where Sahar Yousaf Zai depicts the real life of the people of the tribal areas. He depicts the climate of the areas of district Swat. In his stories, he has presented an inflexible customs of the Pashtoon society. The stories are not fantasy worlds but are the delineation of social injustice. His short story "Sabza Awar Chinaar"is one such story. In some of his stories, he has depicted the valour of the pashtoon people. Moreover, he has pointed towards the hardships of the people of the tribal areas. In some other stories, he has underscored the issue of poverty. His characters are often shown at the mercy of destiny. Though, some shows resistance, yet it proves to be a bubble like resistance. His language is comprehensible conveys his message easily. He was a nature writer and his writings are the representation of life.